Identification of an Aeromonas hydrophila strain as a new mosquito pathogen - Wehbe, Rim; Karaki, Aline; Kambris, Zakaria (Frontiers in Cellular and Infection Microbiology, 2025)
The gut microbiome plays a major role in promoting organismal homeostasis. Mosquito microbiota influences various aspects of host physiology such as immunity, development and vector competence. Most studies addressing mosquito microbiota consist of microbial diversity profiling and rarely investigate the effects of individual bacteria on host physiology. This remains an important gap of knowledge, especially since not all naturally occurring gut microbes are passive commensals. Here, we identify a pathogenic strain of Aeromonas hydrophila that causes mortality to both Culex pipiens and Aedes albopictus mosquitoes upon ingestion. In addition, we show that A. hydrophila breaches the gut epithelium and gains access to the hemolymph. Parallel to gut damage, we detect a significant increase in the number of proliferative cells in the midguts of A. hydrophila fed mosquitoes. Moreover, we find that this bacterium induces a local immune response in the gut leading to the production of anti-microbial peptides. Finally, whole genome sequencing of the isolated strain revealed that it possesses an arsenal of virulence and resistance genes, which provides mechanistic insights into its mosquitocidal activity. This study reports a novel mosquito pathogen and highlights how a bacterial species inhabiting the gut can impact the host’s survival and homeostasis.